Implementing and Learning from a Summer Research Data Management Training Program for Student Researchers - Read, Kevin; Rutley, Sarah (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2024)
This study explores a library-led research data management (RDM) training program at a Canadian post-secondary institution that targeted students working on research projects over the summer. In this paper we describe the program and share findings from a student reflection assignment about completing a data management plan (DMP). Students’ faculty supervisors were required to register them for the program. The training program included four requirements for student participants: attending an introductory RDM session; attending a DMP workshop; submitting a DMP for feedback; and completing a reflection assignment. If participants consented, their reflection assignments were analyzed using a qualitative content analysis approach. Thirty-five faculty supervisors registered 53 students to participate. Thirty-three students completed all components of the program, with 19 providing consent for the analysis of the reflection assignment. Students reported that the benefits of completing a DMP included improved project planning, best practices, data reuse, and team communication. Reported challenges included the inflexibility of DMPs, difficulty populating DMPs, demands on researchers’ time, and lack of long-term value. Fourteen of 19 students reported that building a DMP helped them with their summer projects. Through instruction, practical engagement, and reflection within the context of real-world research, the program supported students in learning about RDM and developing a DMP. Insights for library employees who wish to refine or develop training in their local contexts include the utility of participation incentives such as co-curricular credit, the value of faculty participation in RDM programming for students, and the benefits of collaborating with institutional research offices.